Fig (Ficus carica): A Potential Functional Ingredient for Developing Value Added Products: Fig Added Products (Biological Sciences - PJSIR, 2024)
To increase the intake of fruits and vegetables, especially among young people, the food industry is trying to develop new, ready-to-eat products, such as snacks and breakfast spreads. Nowadays, consumers are choosing their foods based not only on sensory attributes but also on nutritional/functional properties. Fig is the one of the oldest plants cultivated on the earth which is rich in phytochemicals and minerals. The present study was designed to analyze three sun-dried Fig varieties named Afghani, Irani and Turkish for nutritional composition including proximate and minerals (mg/100 g) content and to develop value- added products such as Fig rolls and honey to increase the utilization of Figs in the daily routine. For this purpose, the Fig roll was prepared by filling Fig paste (which was changed gradually from 0 g, 2 g, 3 g,  4 g and 5 g in different treatments) in the chickpea-based dough. Whereas Fig honey was prepared by gradually replacing honey (commercially available) with prepared Fig liquid (from 0%, 20%, 40%, 80%, 100%) in different treatments. Results revealed that the Afghani Fig has the highest protein (4.96%), ash (5.29%), potassium (1148.13), magnesium (198.37) calcium (122.80) and zinc (2.80), whereas the Turkish Fig has a high fiber content (9.38%). However, Fig rolls have 3 g Fig paste filling and the Fig honey prepared with 60% Fig liquid paste was well accepted by consumers for their appearance (8.30, 8.07), flavour (8.53, 7.43), and overall acceptability (8.42, 7.80 respectively) assessed by 9-hedonic scale. The nutrition fact of Fig rolls and honey was also calculated.